Correlation analysis of serum TSG-14 and CORS26 levels with diabetic retinopathy: Serum TSG-14 and CORS26 levels with diabetic retinopathy - Wang, Yuqing; Lin, Shuhua; Yuan, Li; Gao, Xiaojuan; Lin, Lingli; Li, Xiaoqing; Zhang, Zhaode (Journal of Medical Biochemistry, 2026)
Objective To investigate the relationship between serum Cartilage Oligomeric Matrix Protein Like 26 (CORS26), TNF-stimulated gene 14 (TSG-14), and diabetic retinopathy (DR).Methods 276 patients with type 2 diabetes mellitus (T2DM) who were admitted to our hospital between April 2023 and April 2025 participated in a single-center cross-sectional analysis. These patients were divided into a DR group (156 patients) and a non-DR group (120 patients) based on the diagnostic findings. A nonproliferative DR (NPDR) group comprising 98 individuals and a proliferative DR (PDR) group comprising 58 patients were divided from the DR group. The associations between the markers of glycolipid metabolism, TSG-14, and CORS26 were examined using the Pearson method. A logistic analysis was conducted to examine the variables influencing DR in individuals with type 2 diabetes. The diagnostic utility of serum TSG-14 and CORS26 for DR in T2DM patients was assessed using ROC curves.Results The overall information for the two patient groups was similar. While the level of HDL-C was lower than that of the non-DR group, the levels of serum TSG-14, CORS26, TC, TG, LDL-C, and HOMA-IR were higher in the DR group (all P
Keywords: TNF-stimulated gene 14 (TSG-14); Cartilage Oligomeric Matrix Protein Like 26 (CORS26); Type 2 diabetes; Diabetic retinopathy